2010
DOI: 10.1080/01635580903305342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flaxseed Consumption on Urinary Levels of Estrogen Metabolites in Postmenopausal Women

Abstract: Flaxseed is a rich source of dietary lignans. It has been hypothesized that lignans may decrease breast cancer risk through modulation of endogenous hormone levels. The aim of this study was to determine the effect of flaxseed supplementation on urinary levels of estrogen metabolites that may be involved in the development of breast cancer. Forty-three postmenopausal women participated in this 12-wk preintervention-postintervention study. Participants consumed 7.5 g/day of ground flaxseed for 6 wk, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
4
11
1
Order By: Relevance
“…Similarly, there was no change in serum levels of C-peptide after 6 and 12 wk of flaxseed ingestion. As we previously reported (15), there was a suggestion of a decline in total energy intake between the first and second follow-up visits (-96.6 kcal/day, P = .15), consistent with small statistically significant declines in several macronutrients and micronutrients (total fat, total protein, vegetable protein, carbohydrates, total fiber, insoluble fiber, and linolenic acid). The results in Table 2 were essentially unchanged after adjustment for these factors.…”
Section: Resultssupporting
confidence: 84%
“…Similarly, there was no change in serum levels of C-peptide after 6 and 12 wk of flaxseed ingestion. As we previously reported (15), there was a suggestion of a decline in total energy intake between the first and second follow-up visits (-96.6 kcal/day, P = .15), consistent with small statistically significant declines in several macronutrients and micronutrients (total fat, total protein, vegetable protein, carbohydrates, total fiber, insoluble fiber, and linolenic acid). The results in Table 2 were essentially unchanged after adjustment for these factors.…”
Section: Resultssupporting
confidence: 84%
“…Lignans are expected to have beneficial effects in humans after fermentative conversion in the colon to the mammalian lignans ENL and END [13,14]. Subpopulations with higher consumption of lignans display considerable lower disease frequency [7,[15][16][17][18][19][20][21][22]. In several studies, lignan-rich foods, concentrates or partially purified compounds have been shown to improve blood lipids, to enhance glycemic control and to alleviate or cure type 1 and type 2 diabetes [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens are three biochemically distinct molecules the body produces naturally and they include estrone (E1), estradiol (E2), and estriol (E3) (Sturgeon et al, 2010). There is no report in the literature on anti-estrogenic activity of omega-3 from purslane.…”
Section: Anti-estrogenic Action Of Omega-3 Fasmentioning
confidence: 99%
“…Estradiol is the major biologically active estrogen in women. Excessive amounts of estrogen can increase the risk for hormone sensitive cancers such as breast or ovarian cancers (Sturgeon et al, 2010 …”
Section: Anti-estrogenic Action Of Omega-3 Fasmentioning
confidence: 99%